Religious Coping and Emotional Adjustment among Patients Undergoing Dialysis: Treatment Perception as Moderator: Religious Coping and Emotional Adjustment in Dialysis Patients - Aziz, Tahir; Bibi, Humaira; Naz, Summaira; Afsar, Faria Khan (Pakistan Journal of Health Sciences, 2024)
Kidney problems are increasing in world as well as in Pakistan. Waste produced in the human blood is filtered through kidneys. When human kidney fails to operate their functions properly, dialysis is the way people can live the rest of their life. Objective: To explore the moderating role of treatment perception on religious coping and emotional adjustment among patients undergoing dialysis. Methods: Treatment Perception Questionnaire, Brief R-Cope Scale and Emotional Adjustment Measure were used for data collection. 200 dialysis patients; 100 males, 100 females from 19-80 years were selected by using purposive sampling. Results: The results showed significant positive correlation among treatment perception, positive religious coping and emotional adjustment. Treatment perception is significant positive moderator between positive religious coping and emotional adjustment. Positive religious coping and emotional adjustment were greater in older patients, while negative religious coping is greater in younger patients. Female patients have perceived their treatment positively and have greater use of positive religious coping as a result they were more emotionally adjusted than male patients. Additionally, less treatment duration patients have high level of treatment perception, positive religious coping and emotional adjustment than patients having more treatment duration. Conclusions: The findings of this study will help clinical professionals and social workers to have better understanding of these variables, to introduce, promote and modify the required remedies and therapeutic techniques to help out the patients so that they can improve their level of religious coping and emotional adjustment.